2019
DOI: 10.1088/1755-1315/363/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency Monitoring in Textile Industries to Achieve GHG Emissions Reduction Target in Indonesia

Abstract: Modelling is used to provide an outlook and evaluate scenarios related to energy efficiency potentials from end-user in various sectors including industrial sectors. The modelling tools used ExSS (Extended Snap Shot) and GAMS (General Algebraic Modelling System) as solver. Three scenarios were developed to envision Indonesia paths in energy savings potentials, namely business as usual (BaU or baseline) and two counter measure scenarios (CM 1 and CM2). Base year was set to year 2010, in line with NDC scenarios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Implementation of the measures have resulted in 30% decrease in the energy consumption [34]. Retno G.Dewi et al have investigated that mitigating the factors incurred by combined heat systems, lightings, compressed air systems, motor systems, boilers, process integration, steam distribution systems will decrease the energy use for the selected textile industry [35]. After identifying the opportunities for improving the energy efficiency, the suggested measures required are discussed in the following section.…”
Section: Technical Improvement Opportunities In a Typical Textile Ind...mentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of the measures have resulted in 30% decrease in the energy consumption [34]. Retno G.Dewi et al have investigated that mitigating the factors incurred by combined heat systems, lightings, compressed air systems, motor systems, boilers, process integration, steam distribution systems will decrease the energy use for the selected textile industry [35]. After identifying the opportunities for improving the energy efficiency, the suggested measures required are discussed in the following section.…”
Section: Technical Improvement Opportunities In a Typical Textile Ind...mentioning
confidence: 99%
“…Retno G.Dewi at al. has identified that the stream distribution lines have to be insulated well along with correctly placed steam traps [35]. Steam trap selection is the major keyway for uninterrupted operation [43].…”
Section: Energy Efficiency Measures In Wet Processingmentioning
confidence: 99%
“…A study commissioned by the Indonesian government confirms that energy efficiency measures which can be undertaken in the short term can result in a 30% reduction in energy consumption. At 80%, the greatest potential for savings resides in the most energy-intensive processes of "textile finishing" (wet and dry finishing, the process of dyeing and equipment with functionalities) and in the use of more efficient machinery equipment along the entire textile production line [4]. Political guidelines to increase energy efficiency in the industry (annual energy increase of 1% until 2025) along with government programmes for implementation of energy management systems in the textile industry are intended to relieve the emission burden of the Indonesian textile sector, with currently 14 Mt CO2eq of direct and 22 Mt CO2eq of indirect emissions in 2028 [4].…”
Section: Introductionmentioning
confidence: 99%
“…At 80%, the greatest potential for savings resides in the most energy-intensive processes of "textile finishing" (wet and dry finishing, the process of dyeing and equipment with functionalities) and in the use of more efficient machinery equipment along the entire textile production line [4]. Political guidelines to increase energy efficiency in the industry (annual energy increase of 1% until 2025) along with government programmes for implementation of energy management systems in the textile industry are intended to relieve the emission burden of the Indonesian textile sector, with currently 14 Mt CO2eq of direct and 22 Mt CO2eq of indirect emissions in 2028 [4]. To comply with international climate agreements, Indonesia aims to reduce its greenhouse gas emissions from 1990 levels by 29% by 2030 (UNFCCC) and to nearly double the share of electricity generated from renewable sources to 23% by 2025 (2017: 12.5%).…”
Section: Introductionmentioning
confidence: 99%